Anti-tubercular and antioxidant activities of C-glycosyl carbonic anhydrase inhibitors: towards the development of novel chemotherapeutic agents against Mycobacterium tuberculosis. - Zaro, María José (2016)
During the treatment of tuberculosis infection, oxidative stress due to anti-tubercular drugs may result in tissue inflammation. It was suggested that treatment with antioxidant drugs could be beneficial as an adjunct to anti-tuberculosis drug therapy. Recently our group has shown that several C-glycosides are inhibitors of Mycobacterium tuberculosis β-carbonic anhydrases (CAs, EC 4.2.1.1). In an effort to develop novel chemotherapeutic agents against tuberculosis, the anti-tubercular and antioxidant activities of a series of C-glycosides containing the phenol or the methoxyaryl moiety were studied. Many compounds showed inhibition of growth of M. tuberculosis H37Rv strain and good antioxidant ability. A glycomimetic incorporating the 3-hydroxyphenyl moiety showed the best activity profile and therefore this functionality represents lead for the development of novel anti-tubercular agents with dual mechanisms of action.